Singular and regular second order φ-Laplacian equations on the half-line with functional boundary conditions - Fialho, João (2018)
This paper is concerned with the existence of bounded or unbounded solutions to regular and singular second order boundary value problem on the half-line with functional boundary conditions. These functional boundary conditions generalize the usual boundary assumptions and may be applied to a broad number of cases, such as, nonlocal, integro-differential, with delays, with maximum or minimum arguments,... The arguments are based on the Schauder fixed point theorem and lower and upper solutions method.